The Role of Dupilumab in Severe Asthma - Fabio Luigi Massimo Ricciardolo; Francesca Bertolini; Vitina Carriero (Biomedicines, 2021)
Dupilumab is a fully humanized monoclonal antibody, capable of inhibiting intracellular signaling of both interleukin (IL)-4 and IL-13. These are two molecules that, together with other proinflammatory cytokines such as IL-5 and eotaxins, play a pivotal role in orchestrating the airway inflammatory response defined as Type 2 (T2) inflammation, driven by Th2 or Type 2 innate lymphoid cells, which is the major feature of the T2 high asthma phenotype. The dual inhibition of IL-4 and IL-13 activities is due to the blockade of type II IL-4 receptor through the binding of dupilumab with the subunit IL-4Rα. This results in the repression of STAT6 and in the suppression of subsequent de novo formation of several molecules involved in the T2 inflammatory signature. Several clinical trials tested the efficacy and safety of dupilumab in large populations of uncontrolled severe asthmatics, revealing significant improvements in lung function, asthma control, and exacerbation rate. Similar results were reported when dupilumab was employed in patients harboring pathogenetic processes related to T2 immune response, such as atopic dermatitis and chronic rhinosinusitis. In this review, we provide an overview of the recent research in the field of respiratory medicine about dupilumab mechanism of action and its effects.